CONFEDERATION OF EUROPEAN PROBATION - Filip Ciepły (Probacja)
On April 22nd 2024, the Ministry of Justice of the Republic of Poland announced its membership in the Confederation of European Probation (CEP). The article presents the genesis of the CEP, its history, axiological assumptions, goals, organizational structure, areas of activity, achievements, as well as the history of cooperation with entities from Poland.